Vasile Alecsandri’s Adolescence and Youth (Confluenţe Bibliologice, 2016)
The article reﬂects Vasile Alecsandri’s 195th birthday. Writer’s activities. Are described who has been lived in the tumultuous Romania period of building an independent nation.